Governance, conflict, and natural resources in Africa : understanding the role of foreign investment actors - Besada, Hany (McGill-Queen's University Press, 2021)
"A country's abundant natural resources may serve as a curse or a blessing, with the outcome often dependent on prevailing governance structures and experience managing these assets. Despite natural resource advantages, many African countries have failed to transform their enormous economic potential and wealth into tangible benefits such as sustainable socio-economic development, human security, or peace. Governance, Conflict, and Natural Resources in Africa reevaluates the role that foreign state-owned and private-sector actors play in resource-rich states--whether stable, post-conflict, or fragile--in sub-Saharan Africa. Through research and an analysis of in-depth interviews with local stakeholders in Ghana, Sierra Leone, and Ethiopia, Hany Besada explains how foreign state-owned and private sector corporations have contributed to economic growth at both the national and local levels in different resource-rich countries. This book reveals the unique challenges and opportunities created by these investors, demonstrating that adoption policies in business practices and operations have the potential to generate sustainable development and positive economic transformation. Governance, Conflict, and Natural Resources in Africa puts forward a novel framework for understanding the role of private economic actors in extractive industries in Africa and sheds new light on foreign private-sector contributions to capacity building and economic development."--